Study of the damage and failure of the shear ram of the blowout preventer in the shearing process. (December 2015) - Han, Chuanjun; Yang, Xue; Zhang, Jie; Huang, Xianping
Abstract: The blowout preventer (BOP) is one of the most important pieces of well control equipment; the reliability and safety of the shear ram of the BOP significantly affect the control of oil and gas well. Once the BOP fails, a blowout accident may occur, resulting in a great loss of lives and properties. Both a numerical simulation and an experimental investigation the shearing of a drill pipe by shear rams in an emergency situation were investigated. The effects of the inclination angle of the cutting edges, chamfering, the V-shape angle of shear ram, and the diameter and length of the drill pipes were discussed. The study shows that the simulation results of the shearing process are quite consistent with the experimental results. The cross section of the drill pipe gradually becomes oval in shape with the increase in ram displacement due to squeezing. When deformation of drill pipe reaches the fracture criterion, the drill pipe will be torn along the blade surface and then fall off. Von Mises stresses and the plastic strain of the upper and lower rams increase with the increasing displacement of the rams. With the increase of the length and diameter of the drill pipe, the peak stresses of the upper and lower rams gradually decrease. The stresses of the rams first decrease and then increase with the increase in the blade angle, V-shape angle and edge chamfer angle. For the upper and lower shear rams, the optimal blade angles are 4° and 3°, respectively; the optimal V-shape angles are 163° for both rams, and the optimal edge chamfer angles are 45° and 15° for the upper and lower shear rams, respectively. Obvious plastic deformation of the rams' blade edges can be observed and measured after shearing operation. Thus, the shear ram should be checked and assessed before being used again. Highlights: A simulation of the drill pipe shear rams in well control process was completed. Experiments were performed to evaluate the damage to the rams of the shear BOP. Effects of the inclination angle of the cutting edges, chamfering, V-shape angle of shear ram, and the diameter and length of the drill pipes were discussed. Obvious plastic deformation of the blade edges of the rams can be observed and measured after shearing.